Low cost worlds and the airline industry - Garrow, Laurie; Mumbower, Stacey (Henry Stewart Talks, 2009)
Low cost carriers (LCC), Lowering operating costs, Market penetration and growth, Internet booking, Fuel efficiency and fuel expense, Mergers and failure of airlines, Business vs. leisure travelers, Market segmentation, The classical approach, Airline pricing and competition, Differences among LCCs, LCCs strategies, The future of revenue management